Mechanistic Insight into the Antibacterial Activity of Chitosan Exfoliated MoS2 Nanosheets: Membrane Damage, Metabolic Inactivation, and Oxidative Stress - Roy, Shounak; Mondal, Anupam; Yadav, Varnika; Sarkar, Ankita; Banerjee, Ruptanu; Sanpui, Pallab; Jaiswal, Amit (ACS applied bio materials, 2019)
Two-dimensional molybdenum disulfide (MoS2) based nanosheets functionalized or loaded with an antimicrobial agent have recently attracted attention as highly efficient antibacterial agent. MoS2 sheets act as the photothermal transducers in inducing bacterial cell death on impingement of NIR radiation or enabled cell inactivation by wrapping around the cells. However, the intrinsic ability of MoS2 to act as an effective antibacterial agent without the use of any external stimuli or antimicrobial agent is still not well explored. This study provides a detailed mechanism of antibacterial action of chitosan exfoliated MoS2 nanosheets (CS-MoS2) by deciphering the key events happening both at the membrane surface and inside the bacteria as a result of interaction of bacterial cells with the nanosheets. A simple, green, one-step process was employed for synthesizing stable and positively charged MoS2 nanosheets. The prepared nanosheets showed excellent bactericidal activity against both Gram-positive (MIC = 90 μg/mL, MBC = 120 μg/mL) and Gram-negative bacteria (MIC = 30 μg/mL, MBC = 60 μg/mL). Investigations into deciphering the mechanism of action revealed that the CS-MoS2 nanosheets interacted strongly with the bacterial cells through electrostatic interactions and caused rapid depolarization of the membranes through dent formations. On account of strong van der Waals and electrostatic forces occurring between the CS-MoS2 nanosheets and membrane phospholipid molecules, deepening of dents occurred, which resulted in complete membrane disruption and leakage of cytoplasmic contents. This led to inactivation of the bacterial respiratory pathway through inhibition of dehydrogenase enzymes and induced metabolic arrest in the cells. Simultaneously, disruption of the antioxidant defense system of the cells by increased levels of intracellular ROS subjected the cells to oxidative damage and added to the overall bactericidal action. The nanosheets also displayed antibiofilm properties and were found to be compatible with mammalian cells even at high concentrations.